(3eTcGI GdCfhGQ ddSGdcjf eSGdc GdCHQGQs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdMi Gdbjhe GdPi CaGV YdjfG CfhGQkG ef eTcGI GdHQgGf hChQOfG MjGV GdfXQ , acQ YfG ai SQ MbGFb GdYQaGf s
(3BNQgG (B:s
(3hdGHQcI HGdELJeGY , hGddg JGdi jgOi Gdcd Je GdLhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B20s
(3HgG fXGe GdJYbjHIs
(3hgh LhGH ddabjg TgGH GdOjf CMeO Hf Ydi Hf TGaY ef Cgd JgGeIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
Keywords: (3GdJhMjO hGdedd hGdfMds